Penggunaan Media Flashcard Digital untuk Pengenalan Literasi Awal - Hidayati, Novi; Prachagool, Veena (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2025)
This research is motivated by the low interest in reading and writing due to the diversity of media used in early literacy education in early childhood so that it is not uncommon for children to avoid doing literacy activities. This study was conducted to see the use of digital flashcard media to introduce early literacy in early childhood. By using a descriptive qualitative research design involving 8 children in group A and 2 classroom teachers. Data were obtained through observation, and interviews. The data will be analyzed using thematic analysis which consists of recognizing data, generating code, finding themes, reviewing themes, naming themes and then narrating data so as to produce a report. The results of this study show that the use of digital flashcard media can help teachers in introducing early literacy and children look enthusiastic and interested in reading and writing using digital flashcard media because they are presented with sounds, images, and text. So this media is very helpful for children in introducing letters in an easier and more interesting way. However, in the use of digital flashcard media, it is necessary to pay attention to the size, color, and material that will be presented to children. The implication in this study is that this digital flashcard media can be an alternative for educators in introducing early literacy to children before using reading books.